Co-worker dialogue – a tool for health, personal development, and an empowering development culture in the workplace. Issue 1 (1st January 2018) - Nilsson Lindström, Petra; Bringsén, Åsa
ABSTRACT: This study explores managers' perspective on how co-worker dialogue [CWD] can foster co-worker health and personal development, and contribute to an empowering development culture in the workplace. The interview study was performed at a hospital in Sweden. Seventeen hospital managers participated. The managers, both men and women, worked in different areas, and a majority had 30–40 co-workers. To uncover underlying pattern phenomena in the interview data, a six-step inductive qualitative thematic analysis was conducted. The findings present three themes, each highlighting different prerequisites for CWD to function as a resource for the co-workers and the workplace: (1) Utility; (2) Content, and (3) Implementation. The study provides suggestions for and problems of practical implications from the findings. To make the findings useful in other organizations, practical implications are presented and discussed in the light of workplace health promotion [WHP]. The CWD is not focusing on performance the way traditional PA does. The CWD is therefore an important complement to PA in annual co-worker meetings, to also highlight the co-worker perspective. If managers realize the value of working with both PA and CWD, opportunities for health, personal development, and an empowering development culture are created.